PENGARUH MANAJEMEN PENGETAHUAN, BUDAYA PERUSAHAAN DAN KEPEMIMPINAN TERHADAP INOVASI (LITERATURE REVIEW BISNIS KREATIF DAN INOVASI) - Desy Indah Sari; Enru Intan Savisla; Naila Joan Apriliani; Revanya Adinda Putri; Tri Yulaeli (Adisam Publisher, 2025)
Knowledge management, corporate culture, and the influence of leadership on innovation are the focus of this literature study. All things considered, this is an important subject for innovative and imaginative commercial practice. Knowledge management, company culture, and leadership all play an important role in determining the level of innovation. To lay the foundation for future studies, this literature review will analyze the influence of leadership, corporate culture, and knowledge management on innovation. To lay a theoretical foundation for the discussion, this research uses qualitative methodology and literature evaluation to collect theories and expert viewpoints from literature and other sources. Using tools such as Mendeley, Scholar, Google, and others, we will assess online and offline journals owned by library organizations. This literature review found that 1) knowledge management influences innovation, 2) corporate culture impacts innovation, and 3) leadership impacts innovation.